Childhood Asthma: Diagnosis and Treatment - Wim M. van Aalderen (Scientifica)
Many children suffer from recurrent coughing, wheezing and chest tightness. In preschool children one third of all children have these symptoms before the age of six, but only 40% of these wheezing preschoolers will continue to have asthma. In older school-aged children the majority of the children have asthma. Quality of life is affected by asthma control. Sleep disruption and exercised induced airflow limitation have a negative impact on participation in sports and social activities, and may influence family life. The goal of asthma therapy is to achieve asthma control, but only a limited number of patients are able to reach total control. This may be due to an incorrect diagnosis, co-morbidities or poor inhalation technique, but in the majority of cases non-adherence is the main reason for therapy failures. However, partnership with the parents and the child is important in order to set individually chosen goals of therapy and may be of help to improve control. Non-pharmacological measures aim at avoiding tobacco smoke, and when a child is sensitised, to avoid allergens. In pharmacological management international guidelines such as the GINA guideline and the British Guideline on the Management of Asthma are leading.